(untitled) (Stavební obzor - Civil Engineering Journal, 2022)
Topography is one of the important factors affecting the distribution of the self-weight stress field. However, granular materials are different from general continuum materials (such as fluids and solids). Only adopting the continuum theory research still has certain limitations, while the use of experimental methods can better reflect the actual stress state of the granular materials. Therefore, in order to further obtain the vertical self-weight stress distribution of single slope with granular materials, the indoor experimental study of quartz sand based on the point source method is carried out in this paper. The research results indicate that: The measured value of the vertical stress on the bottom surface of the quartz sand slope is generally smaller than the γh (Gravity × Buried depth) value of the corresponding point, and the closer the measuring point is to the slope top, the greater the difference between the test value and γh. Besides, the influence of slope heights and slope ratios on the vertical self-weight stress about slope with granular material is also analyzed. Stress depressions appear in some test conditions, that is, the measured stress peak on the bottom of the slope does not appear at the measuring point closest to the slope top. Whether there is a stress depression and the scope of the depression is mainly related to the slope height, while the slope ratio has little effect on it.